2012
DOI: 10.2217/fon.12.133
|View full text |Cite
|
Sign up to set email alerts
|

Germ Cell Cancer Presenting as Gastrointestinal Bleeding and Developing Brain Metastases: Case Report and Review of the Literature

Abstract: This paper describes a rare case of germ cell cancer with duodenum, brain and lung metastases. The patient presented with melena and left testicle enlargement. Orchiectomy revealed mixed germ cell cancer, enteroscopy revealed duodenal choriocarcinoma, and chest x-ray and computed tomography (CT) showed bilateral lung metastases. The patient received and tolerated cisplatinum-based chemotherapy, and responded well. However, he developed seizures 3 months later. MRI showed brain metastases and he was treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The digestive tract provides a rare but known dissemination area (5%)[ 1 ]. Fu et al[ 6 ] reported the case of a young patient with a symptomatic duodenal metastasis which induced low digestive bleeding. On the other hand, we did not highlight any acute haemorrhagic episode but rather an iron deficiency with chronic haemorrhagic suffusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The digestive tract provides a rare but known dissemination area (5%)[ 1 ]. Fu et al[ 6 ] reported the case of a young patient with a symptomatic duodenal metastasis which induced low digestive bleeding. On the other hand, we did not highlight any acute haemorrhagic episode but rather an iron deficiency with chronic haemorrhagic suffusion.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we did not highlight any acute haemorrhagic episode but rather an iron deficiency with chronic haemorrhagic suffusion. The literature shows that patients presenting with bowel metastasis of an embryonic cancer develop, in most cases, a haemorrhagic symptom (14 out 15 patients in the study by Fu et al[ 6 ]) or a digestive occlusion[ 6 , 7 ]. Tumoural dissemination by contiguity is the most frequently identified tumoural expansion mode at the expense of haematogenic or lymphatic pathways[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result may be related to the fact that patients undergoing surgery generally have a large amount of bleeding and serious condition, and surgical intervention must be taken. 1 [2] 2002 anemia jejunum surgical operation death 2 [3] 2004 haematemesis stomach chemotherapy death 3 [4] 2004 anemia Stomach and colon chemotherapy death 4 [5] 2005 melena Stomach and colon surgical operation+chemotherapy death 5 [6] 2009 melena Intestinum tenue surgical operation+chemotherapy live 6 [7] 2010 melena duodenum chemotherapy live 7 [8] 2011 melena stomach -death 8 [9] 2012 melena duodenum chemotherapy death 9 [10] 2013 melena duodenum chemotherapy live 10 [11] 2013 anemia stomach surgical operation+chemotherapy death 11 [12] 2015 melena stomach chemotherapy live 12 [13] 2019 melena duodenum chemotherapy death 13 [14] 2020 melena duodenum chemotherapy live 14 [15] 2021 melena jejunum surgical operation+chemotherapy death 15 [16] 2021 melena Intestinum tenue surgical operation+chemotherapy death 16 [17] 2021 melena duodenum chemotherapy live…”
Section: Diagnosis and Treatment Processmentioning
confidence: 99%
“…Testicular tumors are the most common solid tumors reported in young males aged 15 -35 years [1,2]. These tumors frequently metastasize to retroperitoneal lymph nodes, but only 5 % of these tumors seed the gastrointestinal (GI) tract [3,4], with the duodenum being the least common site (1.4 %) [4].…”
Section: Metastatic Duodenal Germ Cell Tumor Diagnosed With Endoscopimentioning
confidence: 99%